Autophagy in Immune-Related Renal Disease - Xin Ye; Xu-jie Zhou; Hong Zhang (Journal of Immunology Research)
Autophagy is an important biology process, central to the maintenance of biology process in both physiological and pathological situations. It is regarded as a “double-edged sword”—exerting both protective and/or detrimental effects. These two-way effects are observed in immune cells as well as renal resident cells, including podocytes, mesangial cells, tubular epithelial cells, and endothelial cells of the glomerular capillaries. Mounting evidence suggests that autophagy is implicated in the pathological process of various immune-related renal diseases (IRRDs) as well as the kidney that underwent transplantation. Here, we provide an overview of the pathological role of autophagy in IRRDs, including lupus nephritis, IgA nephropathy, membrane nephropathy, ANCA-associated nephritis, and diabetic nephropathy. The understanding of the pathogenesis and regulatory mechanisms of autophagy in these renal diseases may lead to the identification of new diagnostic targets and refined therapeutic modulation.